Har Dayal : Hindu Revolutionary and Rationalist - Brown, Emily C., (Brill | Manohar Publishers & Distributors, 2023)
... uncovers the reality of Har Dayal as a human force in the political and cultural transformation of India, especially during the period of 1905-19. Not concerned with glorifying or downgrading her subject, Dr. Brown - in a painstaking way, deriving factual evidence from British official documents and other related records - has given us a study which is a true contribution to social science. Har Dayal's patriotic activity in the early part of his adult life accelerated in an explosive manner the departure of English rule from his country, India. He was one of the outstanding leaders of the so-called extremist phase of the Indian independence movement, which was the precursor of the Mahatma Gandhi wave. The scholarly establishment of the importance of this earlier revolutionary phase is presented by Emily C. Brown in this unusual and greatly needed book. - Gobind Behari Lai